Marketing Communication SehatQ Dalam Membangun Brand Awarness Di Media Instagram - Bertha K. Sinambela; Panji (Jurnal Netnografi Komunikasi, 2022)
Instagram is a medium used for publication, anyone can give an assessment in the form ofcomments that affect the company. The purpose of this study was to determine SehatQ's marketing communicationin building brand awareness of Instagram media. The theory in this study is computer mediated communicationand the conceptual basis consists of communication, marketing communication, corporate image, and Instagram.This study uses a qualitative approach and case study methods. The results showed that out of ten activities, onlyeight activities were carried out by SehatQ's marketing communication, namely: product, price, place, promotion,physical condition, process, pressure, and performance. In resolving negative comments that can damage thecompany's image is to carry out regular monitoring, convey clear information, and maximize communication.